Therapeutic effects of different durations of acupuncture on rats with middle cerebral artery occlusion - Zhang, Chao (Neural Regen Res, 2015)
Acupuncture is regarded as an effective therapy for cerebral ischemia. Different acupuncture manipulations and durations may result in different therapeutic effects. In the present study, the Neiguan (PC6) acupoint of rats with occluded middle cerebral arteries was needled at a fixed frequency (3 Hz) with different durations, i.e., 5, 60 and 180 seconds under a twisting-rotating acupuncture method. Results showed that different durations of acupuncture had different therapeutic effects, with 60 seconds yielding a better therapeutic effect than the other two groups. This duration of treatment demonstrated rapid cerebral blood flow, encouraging recovery of neurological function, and small cerebral infarct volume. Experimental findings indicated that under 3 Hz frequency, the treatment of needling Neiguan for 60 seconds is effective for ischemic stroke.